Dead Pixels Seasons 1 & 2 [videorecording (DVD)]. - Davies, Alexa; Merrick, Will; Ritchie, Charlotte; Yelda, Sargon; Mumeni, David (Warner Bros., 2021)
Meet Meg, Nicky, and Usman all of whom are obsessed with the online game Kingdom Scrolls. In Season One, Meg would happily cut a date short to go home and defend Castle Blackfinger; Nicky thinks the miscasting of Vince Vaughn as Tarnadarl in the Kingdom Scrolls movie is an international outrage, and Usman has made a plywood lid for his child's cot, so he can play the game in peace. In Season Two, the Kingdom Scrolls expansion pack has arrived! However, our gaming fanatics' excitement is quashed when they discover that the game they love so much has been commercialized and overrun by a younger generation of players. Meg starts to wonder whether it's time for her to grow up and move on; Usman goes to increasing extremes to hide his gaming from his wife, and Nicky falls for a girl online whom he invites to come and stay. Which doesn't cause any issues between him and Meg, because they don't have feelings for each other.